Mediterranean versus Atlantic monk parakeets Myiopsitta monachus: towards differentiated management at the European scale. Issue 4 (19th February 2019) - Postigo, Jose‐Luis; Strubbe, Diederik; Mori, Emiliano; Ancillotto, Leonardo; Carneiro, Inês; Latsoudis, Panagiotis; Menchetti, Mattia; Pârâu, Liviu G; Parrott, Dave; Reino, Luís; Weiserbs, Anne; Senar, Juan Carlos
Abstract: BACKGROUND: The monk parakeet Myiopsitta monachus (Boddaert), native to South America, is an invasive species in several European countries, causing crop damage and potential negative impacts on wildlife. Only Spain and Great Britain have regulations to control monk parakeets, thus fast growth and spread of populations are likely to occur on a wide scale. The aims of this research are to update information on the distribution and population size of monk parakeets in Europe, assess whether differences in population growth or spread rate exist between populations, and provide recommendations to decision‐makers. RESULTS: Our study estimates that there are 23 758 monk parakeets in the wild, across 179 municipalities in eight European Union (EU) countries; 84% of these municipalities hold between 1 and 100 monk parakeets. All countries with a representative historical record are experiencing exponential growth of monk parakeets. Mediterranean countries are experiencing higher exponential growth, spread rate and faster colonization of new municipalities than Atlantic countries. CONCLUSIONS: We recommend that EU Mediterranean countries consider declaration of the monk parakeet as invasive alien species of regional concern, and develop coordinated efforts to monitor and manage the species, taking advantage of the low population sizes in most municipalities. © 2019 Society of Chemical Industry Abstract : European populations of monk parakeet grow and spread differently according to the biogeographical region they occupy. We propose early action using a differentiated management suitable for these regions.